Charged linker sequence modulates eukaryotic heat shock protein 90 (Hsp90) chaperone activity - Tsutsumi, Shinji; Lee, Chung-Tien; Mayer, Matthias P. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Hsp90 is an essential and highly conserved modular molecular chaperone whose N and middle domains are separated by a disordered region termed the charged linker. Although its importance has been previously disregarded, because a minimal linker length is sufficient for Hsp90 activity, the evolutionary persistence of extensive charged linkers of divergent sequence in Hsp90 proteins of most eukaryotes remains unexplained. To examine this question further, we introduced human and plasmodium native and length-matched artificial linkers into yeast Hsp90. After evaluating ATPase activity and biophysical characteristics in vitro, and chaperone function in vivo, we conclude that linker sequence affects Hsp90 function, cochaperone interaction, and conformation. We propose that the charged linker, in addition to providing the flexibility necessary for Hsp90 domain rearrangements—likely its original purpose—has evolved in eukaryotes to serve as a rheostat for the Hsp90 chaperone machine.